Integrating mechatronic thinking and multi-agent approaches - Foehr, Matthias (2014)
The paper introduces a concept for the combination of mechatronic unit and multi-agent system approaches. It highlights how combining both approaches to a new kind of integrated system architecture may enforce the dissemination and reusability of methods and automatisms developed for one specific system architecture to other similar ones. Additionally it will show how this integrated architecture leads to a better exchange of Automation architectures in general. Thus, all systems compliant with the described architecture may benefit from methods and automatism applicable for a broad range of systems. The suitability of this integration approach is verified by using the example of a washing machine production line.